O Kościele katolickim bez namaszczenia - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2018)
In these considerations, I refer to examples of such a statement about the Catholic Church without anointing, which is not only a testimony of a lack of faith in his help in achieving salvation, but also a deep conviction that he is affected by serious illnesses. This expression was differently motivated, and it had and has very diverse consequences – both for those expressing their words and for the addressees. In each case, however, it meant and signifies the specific votum of the former separatum towards the Catholic Church, and put in the role of complicit all those who, despite revealing serious ills, agree to remain in this community, and even express their tacit acceptance of the irregularities occurring in it.
Keywords: Catholic Church; no anointing; reformers; philosophers; ex-priests